Toward an Ultra-Wideband Hybrid Metamaterial Based Microwave Absorber - El Assal, Aicha (Micromachines (Basel), 2020)
In this paper, we propose a novel design of an ultra-wideband hybrid microwave absorber operating in the frequency range between 2 GHz and 18 GHz. This proposed hybrid absorber is composed of two different layers that integrate a multiband metamaterial absorber and a lossy dielectric layer. The metamaterial absorber consists of a periodic pattern that is composed of an arrangement of different scales of coupled resonators and a metallic ground plane, and the dielectric layer is made of epoxy foam composite loaded with low weight percentage (0.075 wt.%) of 12 mm length carbon fibers. The numerical results show a largely expanded absorption bandwidth that ranges from 2.6 GHz to 18 GHz with incident angles between 0° and 45° and for both transverse electric and transverse magnetic waves. The measurements confirm that absorption of this hybrid based metamaterial absorber exceeds 90% within the above-mentioned frequency range and it may reach an absorption rate of 99% for certain frequency ranges. The proposed idea offers a further step in developing new electromagnetic absorbers, which will impact a broad range of applications.